Considerations about the conditions of life of disabled people from a basic unit of health of an outlying area of the municipality of São Paulo - Aoki, Marta; Corrêa Oliver, Fátima; Maris Nicolau, Stella (O Mundo da Saúde, 2011)
This is situational diagnosis on the conditions of life of disabled people, developed in partnership by a unit of health and the university, which has subsidized the creation of welfare alternatives in rehabilitation in a communitarian context. From data of communitarian agents of health, 53 people with physical, intellectual and sensorialdeficiencies have been identified. From these, 48 have been interviewed (9 children, 27 adults and 12 old women) and invited to speak on: age, type of deficiency, conditions of health, rehabilitation, schooling, work, rent, leisure, communitarian participation and social network. The adults (27 subjects) from 18 to 60 years have prevailed, with physical and intellectual deficiencies. Most women reflected on the feminine condition and their having less opportunities of social participation. Among children, those with sequels of chronic encephalopathy are outstanding. Children and adolescents were inserted in regular education, but with problems in school. The adults presented a low degree of schooling and experiences of work that demand little qualification. From the families interviewed, 32 depend on retirement and welfare benefits, and many are in poverty situation. There is fragility of the network of social support, reduced to the nuclear family, and the isolation to domicile is an important data. There are difficulties of access to services of health and rehabilitation. The diagnosis has supported the implementation of strategies of intervention such as homecare, groups of coexistence, activities for promotion of the access to rights and for integration to cultural activities. To know the profile that population is one of the suppositions of the territorial work in rehabilitation and the implementation of public policies.